Ground Support and Reinforcement Design in Deep Underground Excavation Based on Ground Condition with Emphasis on Mining - Rahimi, Behrooz (Curtin University, 2019)
In this thesis, design of ground support system in deep underground mining is taken account into characterising ground conditions and presenting a new classification in deep and hard rocks. A new insight into the diagnosis of ground behaviour modes and identifying failure mechanism was presented. Also, a developed design methodology so-called CUED method (Comprehensive Underground Excavation Design) was proposed. According to this method, a procedure was defined for each step by the determining IPO(Input/processing/output) approach.